Acute Safety of an Open‐Irrigated Ablation Catheter with 56‐Hole Porous Tip for Radiofrequency Ablation of Paroxysmal Atrial Fibrillation: Analysis from 2 Observational Registry Studies. (9th April 2014) - OZA, SAUMIL R.; HUNTER, TINA D.; BIVIANO, ANGELO B.; DANDAMUDI, GOPI; HERWEG, BENGT; PATEL, ANSHUL M.; POLLAK, SCOTT J.; WANG, HUIJIAN; FISHEL, ROBERT S.
Acute Safety from 2 AF Ablation Registries Introduction This report presents safety data on the use of a new open‐irrigation radiofrequency ablation (RFA) catheter with a 56‐hole porous tip in 742 patients enrolled in 2 US prospective, multicenter observational registry studies representing real‐world use of the catheter. Methods This analysis is comprised of patients who underwent RFA of drug‐refractory recurrent symptomatic paroxysmal atrial fibrillation (AF). Acute adverse events (AEs) were collected and categorized by seriousness, timing, and relatedness, with 7 days of follow‐up data in one study and at least 120 days of data from a 1‐year follow‐up in the other. Acute serious adverse events (SAEs) that were identified as potentially related to the device and/or procedure were adjudicated by an independent safety committee. Results A total of 30 patients (4.0%) in the combined studies experienced an acute SAE related to the device and/or procedure, which was similar in the subset of patients age 65 and over (4.2%). These SAEs included 1.2% cardiac tamponade/perforation, 0.7% pericarditis, 0.5% pulmonary events, and 0.8% vascular access complications. No myocardial infarction, stroke, transient ischemic attack, or atrioesophageal fistulas within 7 days postprocedure were reported. In the study with extended follow‐up, 1 pulmonary vein stenosis and 1 esophageal injury were seen beyond 7 days postprocedure (0.2% each). There were no device or procedure related deaths. Conclusion Results from 2 large observational studies demonstrated that a new porous tip RFA catheter was safe for the treatment of drug refractory, recurrent, symptomatic paroxysmal AF, including treatment of older patients (≥65 years).